Pengaruh Penambahan Ekstrak Kasar Daun Kemangi (Ocimum sanctum) Terhadap Histopatologi Otot Ikan Mas (Cyprinus carpio) yang Diinfeksi Bakteri Aeromonas hydrophila - Atika Marisa Halim; Febi Nadhila Nurin; Mochammad Heri Edy (Politeknik Kelautan dan Perikanan Sorong, Indonesia, 2022)
Basil plant is one of the plants with a distinctive and pungent smell which is used as a traditional medicine. This study aims to determine the effect of crude extract of basil (Ocimum sanctum L. L.) leaves on muscle histopathological of carp (C. carpio) infected with Aeromonas hydrophila. This research was conducted at the Laboratory of Fish Parasites and Diseases, Faculty of Fisheries and Marine Sciences, Universitas Brawijaya, Malang and Histopathology Laboratory, BKIPM I Juanda, Surabaya. This study used a completely randomized design (CRD) with four treatment levels of crude extract of basil leaves . Treatment A (50 ppm), B (150 ppm), C (250 ppm), and D (350 ppm). The forms of muscle tissue damage caused by Aeromonas hydrophila that have been observed are edema, vacuolization, and necrosis. Based on the results of the study, the dose that gave improvement to muscle tissue was at dose D (350 ppm), with the administration of crude basil extract at a dose of 350 ppm known to restore the muscle tissue in carp as in normal fish before being infected with A. hydrophila. Treatment D (350 ppm) showed the lowest damage score, and the structure refers to normal tissue. The higher dose of extract given, it is suspected that the higher compound contained basil leaves to inhibit A. hydrophila infection.